Analyzing requirement prioritization techniques based on the used aspects - Hujainah, Fadhl; Rohani, Abu Bakar; Al-haimi, Basheer; Abdullah, Nasser (MedWell, Journal, 2016)
Requirement prioritization is a critical activity in the system development life cycle, since it aims at assuring the satisfaction level of the project’s stakeholders by identifying the most significant requirement. Prioritization process can be performed using different techniques based on various aspects such as value, time, complexity and importance. Aspects of requirement prioritization play a key role in the success of the prioritization, since it declares the aim of prioritizing the requirements in the techniques. In addition to that, it impacts the quality of the prioritization result. However, majority of existing requirement prioritization techniques do not support these aspects comprehensively. Thus, the purpose of this study is to review the aspects that are considered in the requirement prioritization as well as critically utilizing the existing techniques of requirement prioritization based on the used aspects in the prioritization process in order to support the experts and software industry thus improving the quality of the prioritization process in the techniques. The expected result of this study is to display categorization of requirement prioritization aspects and the implemented aspects with existing requirement prioritization techniques will be presented based on the analysis result. Not only that but it will also highlight factors that impact the implementation of these aspects in the requirement prioritization process. Moreover, this study identifies limitations of the existing techniques with aspects of requirements prioritization and provides future enhancements to overcome the identified limitations.